REKONSTRUKSI PENCATATAN PERKAWINAN PENGHAYAT KEPERCAYAAN PADA MASYARAKAT HUKUM ADAT BERBASIS KEADILAN SOSIAL PANCASILA - Fitri, Dini Amalia; Mundakir, Akhmad (Universitas Stikubank, 2025)
Indonesia is an archipelagic country rich in ethnic, cultural, religious, and belief diversity. The Indonesian Constitution guarantees freedom of religion and belief, yet adherents of traditional beliefs often face discrimination, particularly in marriage registration. This study aims to evaluate and reconstruct the marriage registration system for adherents of traditional beliefs based on Pancasila's social justice principles. The study employs various theories, including the theory of equal freedom of belief, affirmative action, the legal duty to collect what is scattered, and the principle of iustitia socialis. The findings indicate that the integration of marriage registration institutions, simplification of the registration process, training for registration officers, revision of inclusive regulations, and increased public awareness are crucial to overcoming discrimination and ensuring social justice. The implementation of this reconstruction is expected to provide legal certainty and protection of the rights of traditional belief adherents, reflect Pancasila values, and create a more just and inclusive society.